The Impact of Diversity and Inclusion Initiatives on Organizational Culture and Performance - Mariana, Lina (Penelitian dan Pengembangan Ilmu, 2024)
Diversity and inclusion initiatives in the workplace have a significant role in influencing organizational culture and employee well-being. This research aims to explore the impact of these initiatives on employees' perceptions of fairness and well-being in the workplace. The research method uses a systematic approach by applying the PRISMA method to identify and evaluate relevant literature. The research results show that effective implementation of diversity and inclusion can improve organizational justice and employee well-being, with practical implications for the development of more inclusive and equitable human resource management policies and practices.